БИОХИМИЧЕСКИЕ ПОКАЗАТЕЛИ КРОВИ КАРАКУЛЬСКИХ ОВЕЦ РАЗНЫХ ОКРАСОК И ПРОИСХОЖДЕНИЯ - Омонов, М.И. (SCIENCE and SOCIETY, 2019)
Biochemical blood parameters, reflecting changes in the body of animals, allow us to give a biological assessment of animals of different colour and origin. Potassium in metabolism is closely related to water metabolism and acid-base balance in the body, providing a normal level of water balance and osmotic pressure
Keywords: karakul breed; potassium level; concentration; potassium in the blood; low LH type; high NK type